Assessing the ecological sustainability of a forest management system using the ISO Bowtie Risk Management Assessment Tool - B.E. Kishchuk; I.F. Creed; K.L. Laurent; S. Nebel; D. Kreutzweiser; L. Venier; K. Webster (The Forestry Chronicle)
The boreal zone is at risk of cumulative effects of natural resource extraction activities, which may be further exacerbated in the face of climate change. A major challenge is the lack of common approaches to assess the effectiveness of management measures (e.g., acts, regulations, standards, guidelines, best management practices and certification systems) to determine if the policy objective of sustainable management of the boreal zone is being met. The International Organization of Standardization (ISO) 31000 Risk Management Standard and ISO 31010 Bowtie Risk Management Assessment Tool provide a recognized and credible approach for analyzing risk of policy failure, by articulating: (1) the “risk pathway”, linking the pressures, effects and impacts based on science; (2) the performance of the system of management measures in reducing risk; and, (3) the interactive nature of management measures in the presence of escalating factors, including climate change. Here we present the first application of the Bowtie tool in terrestrial ecosystem management by examining forest management pressures and impacts on water quality and biodiversity. We provide a policy analysis tool with potential for addressing risks associated with the future sustainability of the boreal zone.